Social approaches to an industrial past : the archaeology and anthropology of mining - Knapp, Arthur Bernard; Pigott, Vincent C.; Herbert, Eugenia W. (Routledge, 1998)
Social Approaches to an Industrial Past addresses the social issues of mining communities in research spanning a period of 4,500 years. The volume considers themes which are relatively new to archaeology: * the social context of production * gender * power and labour exploitation * imperialism and colonialism * production and technology.